Actin Paracrystals Display Double Schottky Diode-Like Electrical Behavior - Cantiello, Horacio Fabio (2023)
Actin filaments are abundant intracellular polymers implicated in cell motility and contraction. Actin also forms paracrystalline structures under various conditions, including lanthanides and other high ionic strength conditions. Here we tested the electrical properties of purified actin paracrystals induced by either MgCl2 or GdCl3. Tight electrically seal-voltage-clamped crystals displayed strong rectification with a nonlinear conductance under symmetrical and biionic conditions, including 20 mM GdCl3/140 mM KCl and 10 mM MgCl2/140 mM KCl. Rectification was observed in symmetrical ionic conditions with positive-to-negative conductance ratios ranging from 4.18 to 9.00 nS. The current-to-voltage relationships could be fitted with theoretical double Schottky equations and resembled the behavior of semiconducting nanotubes. The highly nonlinear electrical properties of paracrystalline actin arrays may help explain the physiology of actin-rich cellular compartments, such as stereocilia of the cochlea and neuronal dendritic spines also suggest potentially relevant nano-technological properties of this protein.